Let's call the two numbers x and y.
We know that x+y = 842 and that x-y = 314
Now that we have two equations, we can solve using substitution by solving for one variable in one of the equations, and plugging that in for the same variable in the other equation.
Lets solve for x in the second equation to get:
x = 314 + y
Now plug in 314+y for x in the first equation:
(314 + y) + y = 842
Combine like terms:
314 + 2y = 842
Now solve for y:
2y = 842-314
2y = 528
y = 264
Finally, plug 264 in for y to solve for x:
x + 264 = 842
x = 842-264
x = 578
The two numbers are 578 and 264.